Transesophageal echo phase imaging for localizing accessory pathways during adenosine-induced preexcitation in patients with the Wolff-Parkinson-White syndrome - Kücherer, Helmut; Gaspar Carvalho da Silva, Kleber; Melichercik, Juraj; Schützendübel, Rudolf; Beyer, Thorsten; Brachmann, Johannes; Kübler, Wolfgang (The American journal of cardiology, 1996)
Transesophageal phase images and precordial electrocardiograph (ECG) were used to localize accessory pathways during adenosine-induced preexcitation in 30 patients (18 men, mean age ± SD 33 ± 14 years) undergoing endocardial mapping for suspected Wolff-Parkinson-White syndrome. Digitized 2-dimensional echocardiographic cine loops were mathematically transformed using a first harmonic Fourier algorithm before and after catheter ablation. Endocardial mapping found single accessory pathways with anterograde conduction in 20 patients, concealed pathways in 7, and atrioventricular reentry circuits in 3 patients. At baseline, precordial ECG correctly localized 8 pathways (40%) with anterograde conduction and predicted 5 adjacent locations (25%), but findings were normal in 7 patients (35%). Phase imaging correctly identified only 3 pathway locations (15%), findings were normal in 15 (75%), and could not be obtained in 2 patients (10%). Adenosine augmented manifest but minimal preexcitation in 9 patients and unmasked latent preexcitation in 7. In 4 patients, preexcitation was already maximal at baseline. During adenosine-augmented preexcitation, ECG correctly identified 13 locations (65%), but still predicted 7 adjacent locations (35%). However, phase imaging correctly identified 15 locations (75%) and predicted only 3 adjacent locations (15%). All midseptal (n = 2) and anteroseptal (n = 2) locations were correctly identified by phase imaging, but none by ECG. On follow-up studies in 16 patients, successful catheter ablation (n = 13) was equally well confirmed by ECG and phase imaging. Therefore, transesophageal echocardiographic phase imaging during adenosine-induced preexcitation is a readily available and safe procedure that appears clinically most useful for identifying septal pathways.